On Modelling of Data-Driven Monotone Zero-Order TSK Fuzzy Inference Systems using a System Identification Framework - Chin, Ying Teh; Yi, Wen Kerk; Tay, Kai Meng; Chee, Peng Lim (IEEE, 2018)
Chin Ying Teh, Yi Wen Kerk, Kai Meng Tay, and Chee Peng Lim